Adaptive Moderation in Islamic Education: A Study of NU Teachers in Muhammadiyah-Affiliated Schools - Winda Islamitha Nurhamidah Nurhamidah; Muqowim Muqowim (Journal of Indonesian Islamic Studies, 2026)
This study investigates how religious moderation is practiced as an adaptive process by Islamic Education (PAI) teachers affiliated with Nahdlatul Ulama (NU) working in a Muhammadiyah-based primary school. It addresses a gap in existing studies that largely emphasize normative and policy-oriented perspectives of moderation, while paying limited attention to teachers’ lived experiences, identity negotiation, and pedagogical practices in cross-traditional educational settings. A qualitative case study was conducted at SD Muhammadiyah 2 Samarinda from March to April 2026, involving three purposively selected PAI teachers. Data were collected through direct observation, semi-structured online interviews via Zoom, and documentation, and analyzed using an interactive model combined with thematic coding. The findings reveal that teachers’ religious understanding is grounded in the Qur’an and Hadith, accompanied by selective acceptance of intra-Islamic differences within the domain of furu’iyah. Social interaction with non-Muslims is allowed within worldly affairs, while clear theological boundaries are maintained. Moderation is understood as a balanced stance that integrates doctrinal commitment with social tolerance. In classroom practice, moderation is implemented through the integration of theological instruction and values of respect, supported by exemplification of prophetic conduct. Teachers also demonstrate the ability to maintain their NU-based identity while adapting to the Muhammadiyah institutional environment. These findings indicate that religious moderation operates as a context-dependent and dynamic process shaped by textual commitment, social interaction, and pedagogical strategies, conceptualized in this study as “adaptive moderation,” contributing to a more practice-oriented understanding of moderation in Islamic education.